"2032 is a dream for us": exploring amputee football players` understanding of classification in para sport and its application to amputee football - Esatbeyoglu, F.; Gultekin, B.; Kayiran, H. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: The goal of the Para sport classification is to group athletes with a similar impairment into classes to increase participation and promote fair competition by minimizing the impact of eligible impairment on the outcome of competition. Despite its popularity, amputee football is not recognized as one of the Para sports by the International Paralympic Committee (IPC) due to it is lack of an evidence-based classification system. Therefore, the aim of this study was to explore the views of amputee football players on classification in Para sport and how it can be applied to amputee football. METHODS: Semi-structured one-to-one dept interviews were conducted with 12 amputee football players (11 outside, 1 goalkeeper) aged 28.2 ± 5.57 years with 8.4±5.12 years amputee football sport experience. The participants` amputation levels were reported as transhumeral (n=1), knee disarticulation (n=3), transtibial (n=3), and transfemoral (n=5). Hermeneutic phenomenological analysis was used to capture the understanding of amputee football players views on Para sport classification and its application to amputee football for future direction. Transcribed interviews were analyzed inductively, followed by a deductive analysis. RESULTS: Four themes were identified based on our analysis: (1) effect of amputation level, (2) meaning of amputation cause (acquired vs congenital), (3) lack of knowledge related to Para sport classification, and (4) its application amputee football classification. CONCLUSION: The findings of this study suggest the need for a multidisciplinary scientific approach in order to establish an evidence-based classification system in amputee football. The international governing body of amputee football should be encouraged to initiate a fair classification system in amputee football according to the requirements by the IPC.